2021
DOI: 10.3390/ani11102781
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary and Microbial Fatty Acids in the Control of Inflammation in Neonatal Piglets

Abstract: Excessive inflammation and a reduced gut mucosal barrier are major causes for gut dysfunction in piglets. The fatty acid (FA) composition of the membrane lipids is crucial for mediating inflammatory signalling and is largely determined by their dietary intake. Porcine colostrum and milk are the major sources of fat in neonatal piglets. Both are rich in fat, demonstrating the dependence of the young metabolism from fat and providing the young organism with the optimum profile of lipids for growth and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
(218 reference statements)
1
4
0
Order By: Relevance
“…Colostrum is rich in sugars, sugar phosphates, lipids, and amino acids to provide the piglet with easily accessible energy sources and building blocks ( Metzler-Zebeli, 2021 ), which our data confirmed. Numerous metabolites detected in colostrum play roles in cell growth and differentiation as well as gut closure and protection against oxidative stress (e.g., purines and pyrimidines and biogenic amines; Schlimme et al, 2000 ; Gill et al, 2011 ; Chai et al, 2022 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Colostrum is rich in sugars, sugar phosphates, lipids, and amino acids to provide the piglet with easily accessible energy sources and building blocks ( Metzler-Zebeli, 2021 ), which our data confirmed. Numerous metabolites detected in colostrum play roles in cell growth and differentiation as well as gut closure and protection against oxidative stress (e.g., purines and pyrimidines and biogenic amines; Schlimme et al, 2000 ; Gill et al, 2011 ; Chai et al, 2022 ).…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies analyzing the metabolome of porcine colostrum identified 123 and 116 small molecular metabolites ( Tan et al, 2018 ; Settachaimongkon et al, 2023 ). Various factors, including breed, gestation diet, health status, and environment, seem to influence the colostrum composition ( Picone et al, 2018 ; Quesnel and Farmer, 2019 ; Metzler-Zebeli, 2021 ). For instance, some evidence exists that the parity number of sows affects the composition of the FA profile and nonvolatile polar metabolites in porcine colostrum, too, but previous findings were inconsistent ( Luise et al, 2018 ; Settachaimongkon et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the various species, the present meta-regressions supported the anti-inflammatory effects of probiotics under challenged conditions, which may have subsequently contributed to the upregulation of the mucosal barrier, including the expression of tight junction proteins and other first line of defense genes. Certain G protein-coupled receptors sense fermentation end products, such as short-chain and medium-chain fatty acids [ 24 , 25 ]. Due to the lack of data from the original studies, we can only speculate about the fermentation acids that changed locally in the gut due to the probiotic supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory treatments are one of the first-line therapies for microglia reactivity. Depending on the type of pathogen or insult, pharmacological therapy can be based on the application of antibiotics, factors influencing M1 to M2 phenotype polarization (IL-4, IL-13, and TGF-β); analogs of physiological substances (melatonin, erythropoietin, omega-3 polyunsaturated fatty acids, and many others); or natural, usually plant-derived substances (like, e.g., resveratrol, curcumin) [152][153][154][155][156][157][158]. Enhancing oligogliogenesis, resulting in an increased number of OPCs conferring neurotrophic and immunomodulatory support, might be another way to modulate astrocyte reactivity.…”
Section: Crosstalk Between Neural Cells In the Developing Brainmentioning
confidence: 99%